The Effect of Total Labor and Availability of Philanthropic Capital on Educated Unemployment in Medan City - Putri Ayu Syabrina Siregar; Tri Inda Fadhila Rahma; Aqwa Naser Daulay (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this study is to determine the effect of the number of workers and the availability of modes of philanthropy on educated unemployment in Medan City. Due to the close relationship between economic growth and the high percentage of educated unemployment, there are few job prospects and factors that conflict with employment and education. Medan City has a large population, which leads to a high unemployment rate. High school and post-secondary school graduates are the main targets of the educated unemployment rate. This research uses panel data regression analysis using smart PLS application, which is a quantitative research method that takes secondary data from questionnaires to determine how much influence the independent variables have on the dependent variables. Based on the research findings, The number of workers has a large influence on educated unemployment in Medan city. This shows that the number of workers has control over the existing level of educated unemployment. Educated unemployment is strongly influenced by the availability of charity funds. It can be interpreted that the number of educated unemployment is influenced by the availability of charity wealth. The number of educated unemployment in Medan city will decrease in proportion to the amount of charity capital that can be provided by the Medan city region. Educated unemployment is strongly influenced by the number of workers and the availability of charity funds. The level of educated unemployment can be seen to be influenced by the number of workers and the availability of charity resources.